Heart Rate Variability in Head-Up Tilt Tests in Adolescent Postural Tachycardia Syndrome Patients - Orjatsalo, Maija; Alakuijala, Anniina; Partinen, Markku (Frontiers in Neuroscience, 2020)
Introduction: Postural tachycardia syndrome (POTS) is a suspected dysautonomia with symptoms of orthostatic intolerance and abnormally increased heart rate while standing. We aimed to study cardiac autonomic nervous system functioning in head up tilt (HUT) in adolescents with POTS to find out if parasympathetic tone is attenuated in the upright position. Methods: We compared characteristics of a group of 25 (females 14/25; 56%) adolescents with POTS and 12 (females 4/12; 34%) without POTS aged 9 - 17 years. We compared heart rate variability with high and low frequency oscillations, and their temporal changes in head-up tilt. Results: The high frequency oscillations i.e. HF attenuated in both groups during HUT (P < 0.05), but the attenuation was bigger in POTS (P = 0.04). In the beginning of HUT, low frequency oscillations i.e. LF increased more in POTS (P = 0.01), but in the end of HUT, an attenuation in LF was seen in the POTS group (P < 0.05), but not in the subjects without POTS. There were no associations of previous infections or vaccinations with POTS. Subjects with POTS were sleepier and their overall quality of life was very low. Conclusions: The results imply to an impaired autonomic regulation while standing in POTS, presenting as a lower HF and higher LF in the beginning of HUT and an attenuated LF in the prolonged standing position.